Implementasi Sistem Penerjemahan Bahasa Isyarat dengan Metode Pengenalan Ucapan - Mulyana, Dadang Iskandar; Septiani, Novi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The rapid development of technology certainly brings many benefits to the surrounding environment, several factors are helped by the advancement of technological tools, especially to help people with disabilities, currently people with disabilities, especially the mute, often have difficulty communicating, several factors affect the limited understanding of people with disabilities with the surrounding community, for example, the limited hearing of people with mute. With this background, a tool is needed that is able to translate Indonesian into sign language so that it can help people with disabilities and the community in communicating and living in society. This study uses the speech recognition method in its application, the results of the study reached an accuracy value of 80%.